Are green walls a suitable environmental compensation in densifying cities? Quantifying the urban microclimate effects at the pedestrian level in Sao Paulo - Silva, Priscila Weruska Stark da; Duarte, Denise Helena Silva (PosFAUUSP, 2022)
In the city of Sao Paulo, green spaces are few and uneven. Between 2015-2018, to increase greenery, the municipality promoted green walls as an environmental compensation solution for the loss of urban trees. This study aimed to quantify the impact of these green façades on urban microclimate at the pedestrian level, considering the following variables: air temperature, air humidity, and mean radiant temperature. We reviewed local planning documents and the microclimatic performance of green wall technologies, establishing the effects of wall greening based on simulations — using the ENVI-met V4 Science model. Although the main difference was measured 15 cm far from the walls’ surface, the 60 cm away differences from the green wall were insignificant. The results indicate: (a) the impact of the green walls on outdoor microclimates at the pedestrian level is minimum, and (b) Sao Paulo’s policy for environmental compensation using green walls was poorly supported by scientific evidence. Therefore, green walls are a highly questionable alternative for environmental compensation from the perspective of urban microclimate. As much as promoting green walls for potential benefits is desirable, they are unsuitable to compensate the range of ecosystem services lost by the elimination of trees.